THE EFFECTIVENESS OF COMMUNICATIVE LANGUAGE TEACHING IN TEACHING SPEAKING TO EIGHTH GRADE OF SMPN 1 KARANGREJO IN ACADEMIC YEAR 2015/2016 - RIZKI INTAN SUGIANI; Umdatul Khoirot; Supriadi Supriadi (STKIP PGRI TULUNGAGUNG, 2016)
Speaking is one of the four language skills (listening, speaking,reading, and writing). It means through which learners can communicate withothers to achieve certain goals or to express their opinions, intentions, hopes andviewpoints. In addition, people who know a language are referred to as ‘speakers’of that language. There are many kinds of method for teaching speaking, one ofthem is communicative language teaching method. The reseacrh problem is thereany significant effect of communicative Language Teaching in teaching speakingto the eighth grade students of SMPN 1 Karangrejo in academic year 2015/2016.The objectives of the study is to find out significant effect of communicativelanguage teaching in teaching speaking to the eighth grade students of SMPN 1Karangrejo in academic year 2015/2016.In research the researcher used a quantitative research. The population ofthis research was the eighth garde students at SMPN 1 Karangrejo. It consisted of350 students. The researcher used a purposive sampling. There were 64 studentsas sample of this research. There were 32 students as experimental group and 32students as control group The instrument used in this research is a test. The test isspeaking test especially in descriptive text. The study used technique of t-testbased on Winarsunu to analyze the data. Then the data is analyzed by usingquantitative analysis with the Paired Sample T-Test stated by SPSS 21.0.The finding of effectiveness coefficient of communicative languageteaching in teaching speaking, mean score and standard deviation of experimentalgroup were 73.47 and 5.704, while the mean score of control group was 58.40and the standard deviation was 6.936 There was a significant effect in teachingspeaking by using communicative language teaching to the eighth grade studentsof SMPN 1 Karangrejo in academic year 2015/2016.Finally, it could be concluded that there was significant correlationbetween the students’ mastery of generic structure and their achievement ofreading narrative text. The category of the correlation was enough. The researcherhopes that the result of this research will give advantages, and the student will beable to arrange the narrative text to the right order, and get much information.Key Words: Effectiveness, Communicative Language Teaching Method,Teaching Speaking